2018
DOI: 10.2174/1381612824666180130121946
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infections in Pregnancy: A Focus on Ebola Virus

Abstract: During gestation, the immune response of the placenta to viruses and other pathogens plays an important role in determining a pregnant woman's vulnerability toward infectious diseases. Located at the maternalfetal interface, trophoblast cells serve to minimize the spread of viruses between the host and developing fetus through an intricate system of innate antiviral immune signaling. Adverse pregnancy outcomes, ranging from learning disabilities to preterm birth and fetal death, are all documented results of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Respiratory droplet transmission is the main route of SARS-CoV-2, and it can also be transmitted through contact 3 . Several studies [6][7][8][9] revealed that pregnant women with different viral respiratory illness were at high risk of developing obstetric complications and perinatal adverse outcomes compared to non-gravid women, due to changes of immune responses 10 . According to a previous report of 10 patients with SARS in pregnancy in Hong Kong 11 , SARS-CoV infection could be associated with poor pregnancy outcomes, including critical maternal illness, spontaneous abortion, or maternal death, preterm birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory droplet transmission is the main route of SARS-CoV-2, and it can also be transmitted through contact 3 . Several studies [6][7][8][9] revealed that pregnant women with different viral respiratory illness were at high risk of developing obstetric complications and perinatal adverse outcomes compared to non-gravid women, due to changes of immune responses 10 . According to a previous report of 10 patients with SARS in pregnancy in Hong Kong 11 , SARS-CoV infection could be associated with poor pregnancy outcomes, including critical maternal illness, spontaneous abortion, or maternal death, preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies [6][7][8][9] , pregnant women are at high risk of developing viral infection, such as influenza-A, H1N1, SARS-CoV, MERS-CoV and Ebola virus, and appear to have worse clinical outcomes including maternal mortality, stillbirth, spontaneous abortion, and preterm delivery compared to non-gravid women. However, there is only limited data about the clinical features of COVID-19 during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women and their fetuses represent a high-risk population in light of the COVID-19 outbreak [12][13][14][15][16][17][18][19][20] since viral infections such as influenza [21][22][23][24][25][26][27], varicella [28][29][30][31][32], Ebola [33,34], and measles [35,36] show increased severity in this physiological state. Other coronavirus such as SARS-CoV-1 and MERS-CoV have severe effects to both the mother and the fetus, but vertical transmission has not been proven [37][38][39][40][41] albeit these studies included very few number of cases.…”
Section: Main Textmentioning
confidence: 99%
“…Similarly to SARS-CoV-2, hepatitis C and Ebola viruses belong to the RNA viruses. It has been documented that a small number of hepatitis C and Ebola viruses can be detected in breast milk, raising the possibility that breastfeeding may result in mother-to-child transmission of the virus (11,12). There is no evidence supporting the possibility that SARS-CoV-2 can cross the blood-milk barrier and enter breast milk.…”
Section: Discussionmentioning
confidence: 99%